1999
DOI: 10.3354/meps180081
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic carbon availability and the growth of large marine diatoms

Abstract: To address the question of whether free CO2 can be a growth-limiting nutrient in oceanic waters 3 large marine diatoms, Stephanopyxis palmeriana (Greville) Grunow, Ditylum brightwellij (T. West) Grunow in Van Heurck 1883, and Coscinodiscus sp., were grown in pH-drift experiments under batch culture conditions. The cultures were maintained under quiescent conditions without added buffer in the growth medium, allowing the pH to rise and the free CO2 concentration to fall as growth proceeded. Growth rates were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
2
40
4
Order By: Relevance
“…However, at CO 2 concentrations beyond current atmospheric levels of ∼ 400 ppm, growth rates of P. subcurvata or P. antarctica were CO 2 -saturated. Although a general model prediction suggests that an atmospheric CO 2 increase from current levels to 700 ppm could increase the growth of marine phytoplankton by 40 % (Schippers et al, 2004), our results instead correspond to previous studies which showed negligible effects of elevated CO 2 on various groups of phytoplankton (Goldman, 1999;Fu et al, 2007;Hutchins and Fu 2017). In particular, Trimborn et al (2013) found that increasing CO 2 had no effect on growth rates of Southern Ocean isolates of P. subcurvata and P. antarctica.…”
Section: Discussioncontrasting
confidence: 55%
“…However, at CO 2 concentrations beyond current atmospheric levels of ∼ 400 ppm, growth rates of P. subcurvata or P. antarctica were CO 2 -saturated. Although a general model prediction suggests that an atmospheric CO 2 increase from current levels to 700 ppm could increase the growth of marine phytoplankton by 40 % (Schippers et al, 2004), our results instead correspond to previous studies which showed negligible effects of elevated CO 2 on various groups of phytoplankton (Goldman, 1999;Fu et al, 2007;Hutchins and Fu 2017). In particular, Trimborn et al (2013) found that increasing CO 2 had no effect on growth rates of Southern Ocean isolates of P. subcurvata and P. antarctica.…”
Section: Discussioncontrasting
confidence: 55%
“…) (like results of Goldman, 1999). Cultures of the diatom Chaetoceros muelleri showed lower growth and/or no response in elevated CO2 concentrations (Gao et al, 2012).…”
Section: Resultsmentioning
confidence: 48%
“…This resulted mainly from a very high value in the small fraction, although the reason for the difference between the ϩFe and ϩZnϩFe treatments in this small fraction is unknown. The highest chlorophyll-specific POC production at the end of the incubations was for the ϩZnϩFe treatment in the large fraction, consistent perhaps with carbon limitation of large diatoms at relatively low pCO 2 at the end of the incubation; Zn could allow synthesis of CA and could therefore mitigate the potential CO 2 limitation to which larger cells with longer diffusion paths might be susceptible (e.g., Morel et al 1994;Goldman 1999).…”
Section: Does Addition Of Zn and Fe Together Influence Growth Comparementioning
confidence: 86%
“…Indeed, there Ϫ 3 appears to be an increased demand for Zn, Co, or both, and Cd under low-pCO 2 conditions (Morel et al 1994;Cullen et al 1999). The rate of diffusion of free CO 2 into the cell can be a limitation for some species, even in air-equilibrated seawater (Riebesell et al 1993), a point of particular potential relevance to larger cells (with longer diffusion paths) that might alternatively be directly using HCO (Goldman 1999).…”
mentioning
confidence: 99%